Effect of gonadorelin dose and an additional gonadorelin treatment 2 days after the initiation of Resynch-25 on ovarian dynamics and fertility of lactating Holstein cows - Iago M.R. Leão; Carlos E.C. Consentini; Marcelo S. El Azzi; Everaldo Anta-Galván; Teresita Valdés-Arciniega; Lucas Oliveira e Silva; Roberto Sartori; João Paulo N. Martins (Journal of Dairy Science)
ABSTRACT: Our objective was to improve ovulatory response at the initiation of the Resynch-25 protocol by (1) increasing the dose of GnRH from 100 µg to 200 µg; and (2) giving a second GnRH treatment 56 h after the initiation of the protocol. We considered the experimental d 0 the day of the previous service. The experiment consisted of a 2 × 2 factorial design to compare the main effects of GnRH dose (100 vs. 200 µg) and GnRH treatment times (once vs. twice 56 h apart). A total of 2,111 previous services in 1,438 Holstein lactating cows were used. On d 25, cows were assigned to receive either 100 or 200 µg of GnRH only on d 25 or on d 25 and 56 h later (d 27). On d 32, cows diagnosed as nonpregnant (n = 1,076 services) were classified as with or without a corpus luteum (CL). Nonpregnant cows with a CL continued the Resynch-25 protocol receiving PGF2α treatments on d 32 and 33, followed by a GnRH 32 h later and timed AI 16 h after the last GnRH. Blood samples were collected in a subset of cows on d 25, 32, and 34 to assess serum P4 concentrations. In the same subset of cows, transrectal ultrasonographic examinations were performed on d 25, 29, 34 and 36 to assess ovarian parameters and ovulatory response to the GnRH treatments. The overall ovulatory response at the initiation of the protocol, defined as the ovulation between d 25 and 29, was not affected by days of GnRH treatment and averaged 41.9%. On the other hand, nonpregnant cows treated with the higher GnRH dose had a greater ovulatory response at the initiation of the protocol compared with cows treated with the lower dose (48.0% vs. 36.1%). Despite the increase in ovulatory response at the initiation of the protocol, the GnRH dose did not affect fertility of cows submitted to Resynch-25. Furthermore, the second GnRH treatment on d 27 tended to decrease pregnancy per AI on d 32 after AI (39.0% vs. 43.9%), but no effect of days of GnRH treatment was observed in the subsequent pregnancy diagnosis. The absence of a functional CL on d 25 and ovulation at the initiation of the protocol were positively associated with improved fertility. However, the improvement in fertility of cows ovulating at the initiation of the protocol occurred only in cows with a functional CL on d 25. In summary, despite increasing ovulatory response at the initiation of the protocol, the higher dose did not improve fertility. The extra GnRH on d 27 did not increase ovulatory response at the initiation of the protocol and tended to decrease P/AI 32 d after AI of the Resynch-25. In addition, no additive effect of the higher dose and extra GnRH treatment was observed. Despite the lack of overall treatment effect, the data presented in this study suggest that the identification of CL functionality on d 25 may help to optimize the resynchronization strategy used at nonpregnancy diagnosis to potentially increase fertility of cows reinseminated.